2021
DOI: 10.3389/fmicb.2021.789605
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Antiviral Immune Response by N6-Methyladenosine of mRNA

Abstract: Host innate and adaptive immune responses play a vital role in clearing infected viruses. Meanwhile, viruses also evolve a series of mechanisms to weaken the host immune responses and evade immune defense. Recently, N6-methyladenosine (m6A), the most prevalent mRNA modification, has been revealed to regulate multiple steps of RNA metabolism, such as mRNA splicing, localization, stabilization, and translation, thus participating in many biological phenomena, including viral infection. In the process of virus–ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…M 6 A modification has been proposed to be participated in cardiovascular physiological and pathological processes [ [18] , [19] , [20] ]. However, the vital roles of m 6 A writer METTL3 in high glucose exposure vascular endothelial cells are unknown [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…M 6 A modification has been proposed to be participated in cardiovascular physiological and pathological processes [ [18] , [19] , [20] ]. However, the vital roles of m 6 A writer METTL3 in high glucose exposure vascular endothelial cells are unknown [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing data showed that YTHDF readers regulate the mRNA fate of cellular or viral m6A RNAs. It is described to regulate splicing, nuclear export, cap-independent translation, and decay ( 46 ). To better understand the regulatory effects of m6A machinery on the expression of viral genes or viral replication, the expression level of IE-1 was detected from BmN cells transfected with the wild-type and mutant ie-1 plasmids, and Western blotting assay exhibited a higher IE-1 expression level on the mutant plasmid than wild-type ie-1 , confirming that the presence of m6A sites in the ie-1 mRNA may be related to its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrate that m 6 A modification tightly controls various innate immune responses such as the expression of interferons (IFNs), inflammatory responses, and macrophages and dendritic cells homeostasis. m 6 A can either improve the immune response against pathogens and viruses or tame the immune response to prevent aggressive immunopathological damage [46]. 6 A of these transcripts enhanced their translation in DCs via YTHDF1, thus promoting DCs activation and stimulating DC-mediated T cell activation [49].…”
Section: A and The Innate Immune Responsementioning
confidence: 99%